2015
DOI: 10.1136/bmjopen-2015-007694
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure (SHS) and health-related quality of life (HRQoL) in Chinese never smokers in Hong Kong

Abstract: ObjectiveThe evidence on the effect of secondhand smoke (SHS) on Health Related Quality of Life (HRQoL) is limited. We examined the relation between SHS and HRQoL among Chinese in Hong Kong.MethodsAdult never smokers from a probability sample of three cross-sectional waves (2010, 2012, 2013) of The Hong Kong Family and Health Information Trends Survey who completed the Cantonese-version of Short-Form 12 Health Survey Questionnaire (SF12v2) were included in the data analysis conducted in 2014. Models were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…The amount of harmful substances in the body of secondhand smokers is greater than active smokers, because the toxins inhaled through the breath are not filtered; make them more susceptible to health problems compared to active smokers. On the other hand, although the prevalence rate of smoking among women is relatively low, women and children still have health risks as secondhand smokers due to men smoke at home or public space (Centers for Disease Control and health problem, because it can causes various diseases such as coronary heart disease, stroke, and respiratory disorders in adults, and infant death syndrome in infants and children (Chen et al, 2017). Several studies have also reported a link between cancers and secondhand smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of harmful substances in the body of secondhand smokers is greater than active smokers, because the toxins inhaled through the breath are not filtered; make them more susceptible to health problems compared to active smokers. On the other hand, although the prevalence rate of smoking among women is relatively low, women and children still have health risks as secondhand smokers due to men smoke at home or public space (Centers for Disease Control and health problem, because it can causes various diseases such as coronary heart disease, stroke, and respiratory disorders in adults, and infant death syndrome in infants and children (Chen et al, 2017). Several studies have also reported a link between cancers and secondhand smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Secondhand smoke has been a big problem for human being worldwide as it is well-established as risk factors for many diseases. Many studies have reported that exposure to secondhand smoke can cause various diseases such as coronary heart disease, stroke, respiratory disorders in adults, and infant death syndrome in infants and children [1], also several types of cancers indicated by relative risk value of more than one [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to global burden of disease (GBD) calculation, secondhand smoking contributed 9,316,121 DALYs globally in 2013 [2] and more than 0.6 million premature deaths occur due to non-smokers who becoming passive smokers [1]. Cancer due to secondhand smoking also has an economic impact on society.…”
Section: Introductionmentioning
confidence: 99%
“…In the world, more than 0.6 million premature deaths and 10.9 million disability adjusted life years (DALYs) occur due to non-smokers who becoming secondhand smokers. 1 According to global burden of disease (GBD) calculation, secondhand smoking contributed 9,316,121 DALYs globally in 2013. 2 Secondhand tobacco smoke exposure remains a global health problem with 40% of children and 34% of non-smoking adults exposed and resulting in 603,000 attributable deaths from ischemic heart and other cardiovascular diseases, respiratory disorders, asthma and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 SHS exposure also known as risk factor of various diseases such as coronary heart disease, stroke in adults and infant death syndrome in infants and children. 1 Many diseases related to SHS may cause by there are 4000 harmful chemical compounds contained in the heterogeneous aerosol generated by burning tobacco, including nicotine, tar, cyanide, benzene, cadmium, methanol, ammonia and arsenic. 2 The amount of those harmful substances in the body of secondhand smokers is greater than active smokers, because the toxins inhaled through the breath are not filtered; make them more susceptible to health problems compared to active smokers.…”
Section: Introductionmentioning
confidence: 99%